Thames Tunnel, 1200 feet long, 76 feet below high water mark, was 8 years building & cost 446000. Opened 25 March 1843 - Unknown (Tufts Archival Research Center, 2008)
This illustration is from Charles Knight's,"London," Vol. 3. This image was inserted by Edwin C. Bolles and is not found in the original.